2015
DOI: 10.1073/pnas.1508097112
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin modulates fMRI responses to facial expression in macaques

Abstract: Increasing evidence has shown that oxytocin (OT), a mammalian hormone, modifies the way social stimuli are perceived and the way they affect behavior. Thus, OT may serve as a treatment for psychiatric disorders, many of which are characterized by dysfunctional social behavior. To explore the neural mechanisms mediating the effects of OT in macaque monkeys, we investigated whether OT would modulate functional magnetic resonance imaging (fMRI) responses in face-responsive regions (faces vs. blank screen) evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 57 publications
(82 reference statements)
2
47
0
1
Order By: Relevance
“…Elevated oxytocin levels in both the CNS and periphery are most likely due to the direct effects of exogenous peptide administration, although it is impossible to rule out a contribution from endogenous oxytocin release (50). Finally, functional magnetic resonance imaging (fMRI) studies have demonstrated that intranasal oxytocin produces changes in the activity of several brain areas in humans and macaques (49,56,57), thus supporting other findings of the CNS effects of this neuromodulator (58).…”
Section: Discussionmentioning
confidence: 90%
“…Elevated oxytocin levels in both the CNS and periphery are most likely due to the direct effects of exogenous peptide administration, although it is impossible to rule out a contribution from endogenous oxytocin release (50). Finally, functional magnetic resonance imaging (fMRI) studies have demonstrated that intranasal oxytocin produces changes in the activity of several brain areas in humans and macaques (49,56,57), thus supporting other findings of the CNS effects of this neuromodulator (58).…”
Section: Discussionmentioning
confidence: 90%
“…OT is a well-known modulator of social behavior, and several imaging studies in humans and monkeys have implicated the amygdala in this process (28)(29)(30)(31)(41)(42)(43)(44)(45). Inhaled OT increases OT concentration in the central nervous system and enhances both prosocial preferences and social attention in rhesus macaques (33).…”
Section: Resultsmentioning
confidence: 99%
“…Inhaled OT increases OT concentration in the central nervous system and enhances both prosocial preferences and social attention in rhesus macaques (33). Recently, it has been demonstrated that OT administration modulates hemodynamic activity in the amygdala in rhesus macaques (30), and it has been hypothesized that the primate amygdala may express presynaptic OT receptors (46). If reward value-mirroring by the amygdala is critical for prosocial behavior, we reasoned that directly increasing OT levels in the amygdala would increase the likelihood that monkeys would make prosocial decisions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations